MODELING OF STRESS-STRAIN STATE OF THREE-DIMENSIONAL STRUCTURES BASED ON FINITE ELEMENT METHOD WITH HERMITE INTERPOLATING POLYNOMIAL - Reshevskaya, E. S.; Grebenyuk, S. N. (Radio Electronics, Computer Science, Control, 2024)
The technique of construction of a finite element on a basis of interpolational polynomial of Ermite, realized in a subsystem «КОЭРМА» of a program complex «МIРЕЛА+», intended for the decision of tasks of the theory of elasticity by a method of finite elements is described. For check of reliability of results the test example is submitted as a loaded plate fixed on a contour.